1993
DOI: 10.1111/j.1744-6570.1993.tb00866.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Staffing Practices to Organizational Level Measures of Performance

Abstract: Scholars have noted the relative lack of research on the contribution of effective staffing practices to organizational level measures of performance (Schmitt & Schneider, 1983). We collected survey data from the heads of the HRM departments of 201 organizations regarding the extent of use of five staffing practices supported by the academic literature. We also investigated whether organizations that used more of these practices had higher levels of profitability and sales growth than organizations that used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
245
3
19

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(275 citation statements)
references
References 34 publications
8
245
3
19
Order By: Relevance
“…Productivity increases when best candidates are inducted. Positive relation was found by Terpstra and Rozell (1993) between selection test validation, extensiveness of recruiting and use of formal selection processes and firm profits. Some researchers concluded that there is a positive relation between organizational performance and effective staffing.…”
Section: Recruitment and Selection And Firm Performancementioning
confidence: 96%
See 1 more Smart Citation
“…Productivity increases when best candidates are inducted. Positive relation was found by Terpstra and Rozell (1993) between selection test validation, extensiveness of recruiting and use of formal selection processes and firm profits. Some researchers concluded that there is a positive relation between organizational performance and effective staffing.…”
Section: Recruitment and Selection And Firm Performancementioning
confidence: 96%
“…The efficiency of a firm (Huselid, 1995;Terpstra & Rozell, 1993) and its capability to construct a sustainable advantage to compete (Pfeffer, 1994;Prahalad, 1983) may depend upon whether the practices related to HRM are successfully and properly implemented (Jackson et al, 2003;Adnan & Izzat, 2012). A company's human potentials are very hard to duplicate than duplicating equipment, plant and any product (Flanagan & Despanade, 1996).…”
Section: Role Of Hrm In Organizationsmentioning
confidence: 99%
“…Huseld, 1995;Terpstra & Rozell, 1993). While providing useful information, HR practices cause two potential problems.…”
Section: Participantmentioning
confidence: 99%
“…Por un lado, se encuentran trabajos que tratan sobre prácticas aisladas. En concreto, se han abordado aspectos como la compensación variable (Gerhart y Milkovich, 1990), el reclutamiento y la selección (Tepstra y Rozell, 1993), la evaluación del rendimiento (Borman, 1991) y la formación (Rusell, Terborg y Powers, 1985). Y por otro, trabajos que analizan un conjunto o sistema constituido por este tipo de prácticas (Arthur, 1994;Huselid, 1995;Ichniowski et al, 1997;MacDuffie, 1995;Walton, 1985), que vienen a ser los que se denominan STAR.…”
Section: Fundamentos Teóricos E Hipótesis De Trabajounclassified